Soil Characteristics in Post-Mining Reclamation Zones of a Clay Mine PT Solusi Bangun Indonesia Tbk Cilacap - Prihatnanto, Rendy; Yulianto, Bambang; Wasiq Hidayat, Jafron (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2024)
Former clay mining areas often face soil degradation that makes it difficult for vegetation to thrive, even after reclamation. This study explores the physical and chemical characteristics of soil in the reclaimed land of PT Solusi Bangun Indonesia Tbk in Cilacap, aiming to understand how effective the rehabilitation efforts have been. Soil samples were taken from six locations, chosen based on differences in vegetation cover and land elevation. The analysis focused on physical properties such as pH, moisture content, temperature, specific gravity, and porosity, along with chemical aspects like macronutrient levels and heavy metal content. Results showed that soil pH ranged from neutral to slightly acidic, with moisture content varying across the site. While macronutrients were generally adequate for plant growth, their distribution was uneven. Some heavy metals, particularly cadmium and silver, were found in concentrations above recommended environmental limits, whereas lead and arsenic levels remained within safe thresholds. Overall, the reclamation process has helped improve soil conditions, but additional steps—like adding lime, incorporating organic matter, and applying specific remediation techniques—are needed to boost soil fertility and reduce contamination risks. Continued monitoring and adaptive strategies will be key to sustaining the health of the reclaimed landscape